Robust Electrodes for Flexible Energy Storage Devices Based on Bimetallic Encapsulated Core–Multishell Structures. Issue 14 (29th May 2021) - Li, Yan‐Fei; Ye, Shuyang; Shi, Yan‐Hong; Lin, Jian; Song, Yi‐Han; Su, Yang; Wu, Xing‐Long; Zhang, Jing‐Ping; Xie, Hai‐Ming; Su, Zhong‐Min; Sun, Hai‐Zhu; Seferos, Dwight S.
Abstract: Developing flexible electrodes with high active materials loading and excellent mechanical stability is of importance to flexible electronics, yet remains challenging. Herein, robust flexible electrodes with an encapsulated core‐multishell structure are developed via a spraying‐hydrothermal process. The multilayer electrode possesses an architecture of substrate/reduced graphene oxide (rGO)/bimetallic complex/rGO/bimetallic complex/rGO from the inside to the outside, where the cellulosic fibers serve as the substrate, namely, the core; and the multiple layers of rGO and bimetallic complex, are used as active materials, namely, the shells. The inner two rGO interlayers function as the cement that chemically bind to two adjacent layers, while the two outer rGO layers encapsulate the inside structure effectively protecting the electrode from materials detachment or electrolyte corrosion. The electrodes with a unique core‐multishell structure exhibit excellent cycle stability and exceptional temperature tolerance (−25 to 40 °C) for lithium and sodium storage. A combination of experimental and theoretical investigations are carried out to gain insights into the synergetic effects of cobalt‐molybdenum‐sulfide (CMS) materials (the bimetallic complex), which will provide guidance for future exploration of bimetallic sulfides. This strategy is further demonstrated in other substrates, showing general applicability and great potential in the development of flexible energy storage devices. Abstract : The encapsulated core–multishell structure with an architecture of substrate/reduced graphene oxide (rGO)/bimetallic complex/rGO/bimetallic complex/rGO is used to fabricate robust and high energy density electrodes for lithium/sodium storage, with a high proportion of active material (20 wt%) and mechanical strength. The underlying synergistic effect of bimetal ions is revealed via experimental investigations and theoretical calculations.